Aula universitária : espaçotempo de formação humana - Galleão, Antonio Miranda (2014)
In face of a scenario characterized by privatization and mercantilization of education, this study has the purpose of understanding the meaning and pedagogical possibilities of a university class, considered, within this work, as the core element of the formal teaching and learning process. Based on the assumption that the class influences and is influenced by the environment, a bibliographic / documental research of exploratory character was initially developed, aiming at providing foundation to the theoretical assumptions of this subject of study: the university class. That phase was supported by Almeida; Bernheim; Buarque; Chauí; Cunha, L.; Demo; Freire; Imbernón; Masetto; Neves, C.; Nogaro; Rué; Santos; Silva; Snyders; Teixeira; Zabala and Zabalza. The field research, carried out on students of three Engineering night courses from a Higher Education institution in the Baixada Santista Region, highlighted the voice of students regarding university classes. The qualitative approach research was structured in three stages: first, gathering data on the perception of students regarding the classes already attended before this research was established; second, an action research with the purpose of experiencing classes that moved away from the reproductive class model; and a third stage, aimed at providing reflection on the experience lived by the participants of stage 2. The analysis of data collected in the study was based on the dialectical hermeneutics with operational support of Content Analysis. From the methodological standpoint, the work counted on the following authors: Bardin; Bodgan and Biklen; Ghedin and Franco; Lüdke and André; Franco, M. A; Franco, M. L.; Minayo; Thiollent and Tripp. Data analysis made possible to infer that students that took part in this research also bring with them a concept of class that is compatible with the one established from the theoretical studies: the class as spacetime of human formation, based on the active participation of students and professor; a spacetime in which all participants can learn, which provides incentive to the critic spirit, research, reflection, dialogue; a class that allows the attendee to go beyond the contents studied therein, and that seeks a deeper level of learning. At the end of the work, it was possible to reach the conclusion that the class can constitute a privileged spacetime of human formation, despite the complex and contradictory context of Graduate Higher Education currently made available in Brazil.